THE LATIN LANGUAGE AND CULTURE ON ROMANIAN TERRITORY IN THE 11th – 16th CENTURIES - Halichias, Ana-Cristina (European Scientific Journal, ESJ, 2014)
Unlike the Central and Western Europe, where culture and civilization were expressed through Medieval Latin and native languages (each with their evolution stages), in Transylvania, Moldavia and Wallachia (situated at the crossroads between Orient and Occident) this duality took specific forms in which the Byzantine and Slavonic influences and those of different other western trends blended in an admirable cultural synthesis. This paper follows the most important evolutionary moments of the Latin language on Romanian territory, underlying the fact that, even being mostly under Byzantine and Slavonic cultural influences, Moldavia and Wallachia were (like Transylvania) connected to the western culture of Latin heritage through the contribution of the Catholic Church from the two neighbouring catholic kingdoms (Hungary and Poland) and through the diplomatic relationships with those kingdoms and with Italy, Germany and France.